Dimensions of conscious experience - Pylkkänen, P. (Paavo); Vadén, Tere (Advances in consciousness research, 2001)
It is by now commonly agreed that the proper study of consciousness requires a multidisciplinary approach which focuses on the varieties and dimensions of conscious experience from different angles. This book, which is based on a workshop held at the University of Skövde, Sweden, provides a microcosm of the emerging discipline of consciousness studies and focuses on some important but neglected aspects of consciousness. The book brings together philosophy, psychology, cognitive neuroscience, linguistics, cognitive and computer science, biology, physics, art and the new media. It contains cri.